(untitled) (Journal of the College of Basic Education, 2022)
The current research was determined by male and female teachers of art education, graduates of the College of Basic Education for the academic year 2010-2011, and comprehensive quality standards. The research community consisted of (186) male and female teachers distributed over (164) primary schools affiliated to the First Rusafa Education Directorate for the academic year 2010-2011. Two types of samples were selected from the first (54) male and female teachers, representing (30%) of the original research community (as a survey sample). The second (80) male and female teachers